2011
DOI: 10.1088/0953-8984/23/15/156003
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature antiferromagnetic order in superconducting XyFe2 −xSe2(X = Rb, K): a neutron powder diffraction study

Abstract: Abstract.Magnetic and crystal structures of superconducting X y Fe 2−x Se 2 (X= Rb and K with T c =31.5 K and 29.5 K) have been studied by neutron powder diffraction at room temperature. Both crystals show ordered iron vacancy pattern and the crystal structure is well described in the I4/m space group with the lattice constants a =8.799, c =14.576 and a =8.730, c =14.115Å and the refined stoichiometry x=0.30(1), y=0.83(2) and x=0.34(1), y=0.83(1) for Rb-and K-crystals respectively. The structure contains one f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
52
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 21 publications
(39 reference statements)
4
52
0
Order By: Relevance
“…This signals the presence of frozen magnetic moments on the Fe sites. Hence, we can attribute this contribution to the AF phase observed with neutron scattering measurements [10,17]. Its low-temperature relaxation rate 1/T 1 differs from that of the SC phase, as evidenced in Fig.…”
mentioning
confidence: 74%
“…This signals the presence of frozen magnetic moments on the Fe sites. Hence, we can attribute this contribution to the AF phase observed with neutron scattering measurements [10,17]. Its low-temperature relaxation rate 1/T 1 differs from that of the SC phase, as evidenced in Fig.…”
mentioning
confidence: 74%
“…The value of the ordered magnetic moment of Fe amounts to 3.31 µ B at 11K, which is the largest among all known iron based superconductors [4,5,6]. Recent µSR [7], STM [8] and Raman [9] studies showed a mutual relation between superconductivity and magnetism in these materials.…”
Section: Introductionmentioning
confidence: 99%
“…The recent discovery of block checkerboard antiferromagnetic order of superconducting materials A x Fe 2−y Se 2 , A = K, Rb, Cs and Tl) has invoked considerable debate in the scientific community. [1][2][3][4][5][6] It was shown that the appearance of antiferromagnetism is a consequence of the Fe vacancy ordering. 7,8 These unique properties among the superconductors opened a question whether Fe vacancies stabilize or destroy the superconductivity.…”
mentioning
confidence: 99%